The impact of social mobilization on health service delivery and health outcomes: Evidence from rural Pakistan - Xavier Giné; Salma Khalid; Ghazala Mansuri (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
We use a randomized community development programme in rural Pakistan to assess the impact of citizen engagement on public service delivery and maternal and child health outcomes. The programme had a strong focus on ensuring the participation of women. Women in the study villages had also identified access to primary care as a critical need for them and their children at baseline. At midline, we find that the mobilization effort alone had a significant impact on the performance of village-based health providers. We detect economically large improvements in pregnancy and well-baby visits by Lady Health Workers, as well as increased utilization of pre- and post-natal care by pregnant women. In contrast, the quality of supra-village health services did not improve, underscoring the importance of community enforcement and monitoring capacity for improving service delivery.
Keywords: C93; D7; H75; I11; O12; 330; public service delivery; maternal and child health; citizen engagement; community development; Pakistan; Lady Health Workers